Synthesis of bacterial cellulose by Acetobacter Xylinum sp. using pineapple pith for biocomposite application - Ab. Halim, Nurul Iffah (2010)
Bacterial cellulose produced by Acetobacter xylinum sp. was a new type of biopolymer. It was far superior to its counterpart from plants because of its exceptional purity, ultra fine network structure, high biodegradability and unique mechanical strength. Bacterial cellulose was expected to be used for many industrial applications as a high-strength construction material, food additive and a component of biodegradable products and paper. The objectives of this study were to investigate the production of bacterial cellulose in shaken culture condition and in various value of pH using pineapple pith juice as the substrate for the fermentation process. The shaken culture method had been carried out at 100 rpm, 110 rpm, 120 rpm, 130 rpm and 140 rpm while the pH value was investigated in the range of 4.0 to 8.0. The parameter conditions were fixed at the temperature of 30 ˚C and glucose concentration of 9 g/L for all the experiments in this research. From this research, the bacterial cellulose production in shaken culture at 120 rpm and pH of 6.0 were the most suitable conditions for culture medium because it formed the highest yield that was 14.1860 g. The qualitative analysis with Fourier Transform Infrared (FTIR) shows that the compound of cellulose was detected. As a conclusion, the objectives in this study were achieved by investigated the effect of shaken speed of the stackable incubator shaker and the pH of substrate towards the production of bacterial cellulose using Acetobacter xylinum sp. in the medium of pineapple pith juice.